Pulmonary enteric adenocarcinoma with progression disease after second - line therapy: a case report - Guo, Ya; Zhang, Bin; Zhang, Heng; Gao, Yunbin; Zhao, Haibo; Jiang, Pei; Yu, Qing-Qing (Frontiers in Oncology, 2025)
Pulmonary enteric adenocarcinoma (PEAC, also known as Enteric-type adenocarcinoma of the lung, lung - ETAC) is a rare subtype of non-small cell lung cancer (NSCLC) that has the same morphological and immunohistochemical characteristics as colorectal adenocarcinoma and requires gastroenteroscopy to rule out lesions of enteric origin. As a rare solid tumor in lung cancer, PEAC has unique clinical outcome, imaging, pathological and molecular characteristics, and poor prognosis. However, the molecular characteristics and therapeutic biomarkers of PEAC are unclear, and its treatment remains challenging. In this case, we describe a 61-year-old man diagnosed with advanced primary PEAC with KRAS mutation. In the case of unknown PD-L1 expression status, first-line treatment was given to lung adenocarcinoma regimen (immunotherapy combined with chemotherapy), progression occurred after 2 cycles, and progression-free survival (PFS) was 1.5 months. Then the second-line XELOX regimen (oxaliplatin combined with capecitabine) was adjusted. The lesions were significantly reduced after 2 and 4 cycles, and the disease progressed again after 6 cycles, with a PFS of 4.5 months. Anlotinib targeted drugs were selected for third-line treatment, but considering the overall poor condition of the patient, the patient himself refused further treatment. Finally, after discharge, the patient went to the local hospital for nutritional support and symptomatic treatment. The results suggest that standard first-line therapies (immunotherapy plus chemotherapy) and colorectal cancer regimens may have a relatively limited impact on survival in KRAS-driver positive advanced PEAC.